2017
DOI: 10.1371/journal.pone.0168556
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of Behavioral Deficits with Brain Pathology Assessed through Longitudinal MRI and Histopathology in the HdhQ150/Q150 Mouse Model of Huntington’s Disease

Abstract: A variety of mouse models have been developed that express mutant huntingtin (mHTT) leading to aggregates and inclusions that model the molecular pathology observed in Huntington’s disease. Here we show that although homozygous HdhQ150 knock-in mice developed motor impairments (rotarod, locomotor activity, grip strength) by 36 weeks of age, cognitive dysfunction (swimming T maze, fear conditioning, odor discrimination, social interaction) was not evident by 94 weeks. Concomitant to behavioral assessments, T2-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 66 publications
5
11
2
Order By: Relevance
“…Indeed, we have also observed a decrease in the volume of the total hippocampus as well as of its DG subregion in 6-month-old YAC128 mice. Our results are in accordance with studies in diverse HD transgenic mouse models that have documented reduced cortical, globus pallidus, and hippocampal volumes [ 80 , 86 89 ]. Moreover, in humans, Rosas et al observed atrophy in several brain regions, including the hippocampus [ 85 ].…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, we have also observed a decrease in the volume of the total hippocampus as well as of its DG subregion in 6-month-old YAC128 mice. Our results are in accordance with studies in diverse HD transgenic mouse models that have documented reduced cortical, globus pallidus, and hippocampal volumes [ 80 , 86 89 ]. Moreover, in humans, Rosas et al observed atrophy in several brain regions, including the hippocampus [ 85 ].…”
Section: Discussionsupporting
confidence: 92%
“…Enlargement of the lateral ventricles and cortical shrinkage appear in both human [ 5 , 58 ] and animal models [ 1 , 34 , 73 , 112 ] of dementia. Atrophy of the brain likely results from progressive degeneration of neurons, and the loss of these neurons is a likely contributor to the manifestation of dementia.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in homozygous Q140 mice, stereological techniques revealed no significant atrophy of cortex and only mild volumetric changes in striatum at 12 months of age (Deng, Wong, Wan, & Reiner, ; Lerner, Trejo Martinez Ldel, Zhu, Chesselet, & Hickey, ). In Q150 mice, a recent analysis using structural MRI techniques demonstrated that progressive cortical and striatal volumetric decline can be detected from 3.5 months of age (Rattray et al., ). Accordingly, in Q175 mice the most prominent changes revealed by stereological techniques were detected at 12 months of age (Smith et al., ), but with MRI, the alterations in cortex and striatum were found at much earlier ages (4 months of age), and although sustained up to 12 months, interestingly did not worsen (Heikkinen et al., ; Peng et al., ).…”
Section: Neuropathological Featuresmentioning
confidence: 99%
“…Similar to full‐length mouse models, KI models display a late‐onset motor phenotype directly related to the number of CAG repeats. For example, whereas the Q111 mouse shows few, if any, motor alterations (Menalled et al., ), homozygous Q140 mice display mild motor abnormalities in parameters such as distance in running wheel assessment at 3.5 months of age, but no changes are observed in latency to fall in rotarod or stride length (Stefanko et al., ), whereas Q150 mice show reduced latency to fall in rotarod at 10 months of age and reduced locomotor activity at 17, but reduced grip strength was found much earlier at 3 months (Rattray et al., ). Motor phenotype onset is more evident in Q175 mice: altered coordination in rotarod occurs at 6 to 7 months in both heterozygous and homozygous animals (Menalled et al., ; Smith et al., ; Peng et al., 2014).…”
Section: Behavioral Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation